Making place at the end of the world : an ethnography of tourism and urban development in Ushuaia, Argentina’s Antarctic Gateway City. - Herbert, Andrea (University of Canterbury. LSAPS, Anthropology, 2014)
This thesis is concerned with the lived experience of placemaking in Argentina’s Antarctic gateway port Ushuaia. Based on 12 months ethnographic fieldwork, it explores the relations between tourism, urban development, and socio-economic difference. As such, it investigates how agents from across the social spectrum conceive of, and construct their sense of place “at the end of the world”. As the world’s southernmost city, Ushuaia is attractive to tourists for its stunning landscapes, unique location, and strategic proximity to Antarctica. However, the image of a friendly tourist destination crucial to everyday life in this Patagonian city is contested by its stakeholders. This thesis looks beyond the image presented to tourists to explore frictions among residents, the city council, and touristic enterprises. Ushuaia is revealed as an urban location beset by growing unrest due to issues of population growth and social polarization. This is analyzed in relation to its geopolitical significance for the Argentine state, territorial struggles with Chile, and economic incentives for in-migration. Consequently, this thesis considers the dynamic and shifting character of the city’s population through an engagement with economic and lifestyle migrants, including those dwelling in non-legal settlements, and tourists who occupy Ushuaian space alongside more longstanding citizens. The thesis demonstrates how conflicting views collide regarding issues of urbanization, industrialization, tourism, and environmental conservation, analyzed in relation to the interests and concerns of different social constituencies. Through extensive interviewing with a diverse array of social actors, this thesis also explores the different levels of economic and socio-cultural attachment to Antarctica, suggesting a schism between Ushuaia’s touristic representation, Antarctic alignment, and the needs and interests of its inhabitants. This thesis, then, explains the diverging place-based ideas and aspirations of different social groups in ...